Marble caskets / Putera Rizq Shaharin and Ts. Nik Nor Azidah Nik Aziz - Shaharin, Putera Rizq; Nik Aziz, Nik Nor Azidah (Universiti Teknologi MARA, Kedah, 2024)
Proudly mentioned, the poems featured in this anthology are a testimony to the depth of feelings, spirits, and the tireless solidarity of the authors with the Palestinian people. Each poem written from the depth and breadth of the soul serves as a powerful reminder of the shared humanity that unites us all.